Personalized teleoperation via intention recognition. (3rd July 2018) - Mghabghab, Serge; Elhajj, Imad H.; Asmar, Daniel
ABSTRACT: One of the challenges of teleoperation is the recognition of a user's intended commands, particularly in the manning of highly dynamic systems such as drones. In this paper, we present a solution to this problem by developing a generalized scheme relying on a Convolutional Neural Network (CNN) that is trained to recognize a user's intended commands, directed through a haptic device. Our proposed method allows the interface to be personalized for each user, by pre-training the CNN differently according to the input data that is specific to the intended end user. Experiments were conducted using two haptic devices and classification results demonstrate that the proposed system outperforms geometric-based approaches by nearly 12%. Furthermore, our system also lends itself to other human–machine interfaces where intention recognition is required. Abstract :